Loss of Peripheral Sensory Function Explains Much of the Increase in Postural Sway in Healthy Older Adults - Anson, Eric; Bigelow, Robin T.; Swenor, Bonnielin; Deshpande, Nandini; Studenski, Stephanie; Jeka, John J.; Agrawal, Yuri (Frontiers in Aging Neuroscience, 2017)
Postural sway increases with age and peripheral sensory disease. Whether peripheral sensory function is related to postural sway independent of age in healthy adults is unclear. Here we investigated the relationship between tests of visual function (VISFIELD), vestibular function (CANAL or OTOLITH), proprioceptive function (PROP), and age, with center of mass sway area (COM) measured with eyes open then closed on firm and then a foam surface. A cross-sectional sample of 366 community dwelling healthy adults from the Baltimore Longitudinal Study of Aging was tested. Multiple linear regressions examined the association between COM and VISFIELD, PROP, CANAL, and OTOLITH separately and in multi-sensory models controlling for age and gender. PROP dominated sensory prediction of sway across most balance conditions (β’s = 0.09-0.19, p’s < 0.001), except on foam eyes closed where CANAL function loss was the only significant sensory predictor of sway (β = 2.12, p < 0.016). Age was not a consistent predictor of sway. This suggests loss of peripheral sensory function explains much of the age-associated increase in sway.